2015
DOI: 10.1103/physrevb.91.201110
|View full text |Cite
|
Sign up to set email alerts
|

g-factor modification in a bulk InGaAs epilayer by an in-plane electric field

Abstract: We report on the modification of the g-factor by an in-plane electric field in an In0.031Ga0.969As epilayer. We performed external magnetic field scans of the Kerr rotation of the InGaAs film in order to independently determine the g-factor and the spin-orbit fields. The g-factor increases from −0.4473 ± 0.0001 at 0 V/cm to −0.4419 ± 0.0001 at 25 V/cm applied along the [110] crystal axis. In addition, spatially-resolved spin measurements show a g-factor dependence on diffusive velocity. The change in g-factor … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
3
5
0
Order By: Relevance
“…Note that, for both channel directions, this modification is symmetric on the field polarity (velocity direction). A similar behavior was measured in InGaAs epilayers 25 . However, the high mobility in our system lets us produce a stronger variation of 0.02 when increasing the drift velocity from zero to 10 µm/ns in considerably smaller electric fields.…”
Section: Experimental Measurementssupporting
confidence: 80%
“…Note that, for both channel directions, this modification is symmetric on the field polarity (velocity direction). A similar behavior was measured in InGaAs epilayers 25 . However, the high mobility in our system lets us produce a stronger variation of 0.02 when increasing the drift velocity from zero to 10 µm/ns in considerably smaller electric fields.…”
Section: Experimental Measurementssupporting
confidence: 80%
“…The modification of the g factor by an in-plane electric field was reported recently. For bulk InGaAs epilayers, 53 they measured ∆g = 0.0053 and found that g increases with the drift velocity. For [110] oriented QWs, 54 the electrical variation of the g tensor was also found to depend on the external magnetic field and to increase with the current.…”
Section: Transverse Spin Transportmentioning
confidence: 99%
“…Our data agrees with those reports as the g-factor decreases for electrons that drifted far from the current path. Nevertheless, we reached a variation of ∆g = 0.02 which could indicate a larger change on the drift velocity because ∆g ∝ V 2 d [199]. We noted that, at the longest transverse distance from the current path (y= 0.4 mm), we recovered the g-factor value measured at V d = 0 in Fig.…”
Section: Longitudinal Spin Transportsupporting
confidence: 57%
“…The modification of the g-factor by an in-plane electric field was reported recently. For bulk InGaAs epilayers [199], they measured ∆g = 0.0053 and found that g increases with the drift velocity.…”
Section: Longitudinal Spin Transportmentioning
confidence: 99%